Remembering generations : race and family in contemporary African American fiction - Rushdy, Ashraf H. A., 1961- (University of North Carolina Press, 2001)
This study examines how cultural works contribute to social debates, how a particular representational form emerges out of a specific historical epoch, and how some intellectuals meditate on the issue of historical responsibility within contemporary American society.